Effects of urea plus nitrate pretreated rice straw and corn oil supplementation on fiber digestibility, nitrogen balance, rumen fermentation, microbiota and methane emissions in goats - Xiumin Zhang; Medrano, Rodolfo F.; Min Wang; Beauchemin, Karen A.; Zhiyuan Ma; Rong Wang; Jiangnan Wen; Lukuyu, Ben A.; Zhiliang Tan (Springer, 2019)
Urea pretreatment is an efficient strategy to improve fiber digestibility of low quality roughages for ruminants. Nitrate and oil are usually used to inhibit enteric methane (CH4) emissions from ruminants. The objective of this study was to examine the combined effects of urea plus nitrate pretreated rice straw and corn oil supplementation to the diet on nutrient digestibility, nitrogen (N) balance, CH4 emissions, ruminal fermentation characteristics and microbiota in goats. Nine female goats were used in a triple 3 × 3 Latin Square design (27 d periods). The treatments were: control (untreated rice straw, no added corn oil), rice straw pretreated with urea and nitrate (34 and 4.7 g/kg of rice straw on a dry matter [DM] basis, respectively, UN), and UN diet supplemented with corn oil (15 g/kg soybean and 15 g/kg corn were replaced by 30 g/kg corn oil, DM basis, UNCO).Compared with control, UN increased neutral detergent fiber (NDF) digestibility (P < 0.001) and copies of protozoa (P < 0.001) and R. albus (P < 0.05) in the rumen, but decreased N retention (-21.2%, P < 0.001), dissolved hydrogen concentration (-22.8%, P < 0.001), molar proportion of butyrate (-18.2%, P < 0.05), (acetate + butyrate) to propionate ratio (P < 0.05) and enteric CH4 emissions (-10.2%, P < 0.05). In comparison with UN, UNCO increased N retention (+34.9%, P < 0.001) and decreased copies of protozoa (P < 0.001) and methanogens (P < 0.001). Compared with control, UNCO increased NDF digestibility (+8.3%, P < 0.001), reduced ruminal dissolved CH4 concentration (-24.4%, P < 0.001) and enteric CH4 emissions (-12.6%, P < 0.05).A combination of rice straw pretreated with urea plus nitrate and corn oil supplementation of the diet improved fiber digestibility and lowered enteric CH4 emissions without negative effects on N retention. These strategies improved the utilization of rice straw by goats.